2017
DOI: 10.1038/s41467-017-00932-7
|View full text |Cite
|
Sign up to set email alerts
|

Activating de novo mutations in NFE2L2 encoding NRF2 cause a multisystem disorder

Abstract: Transcription factor NRF2, encoded by NFE2L2, is the master regulator of defense against stress in mammalian cells. Somatic mutations of NFE2L2 leading to NRF2 accumulation promote cell survival and drug resistance in cancer cells. Here we show that the same mutations as inborn de novo mutations cause an early onset multisystem disorder with failure to thrive, immunodeficiency and neurological symptoms. NRF2 accumulation leads to widespread misregulation of gene expression and an imbalance in cytosolic redox b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 49 publications
4
53
0
Order By: Relevance
“…Specifically, isoflavones are a type of naturally occurring isoflavonoids, which act as phytoestrogens in mammals, their targets were mainly distributed in module 1, 2, and 5 ( Supplementary Figure 6 ). Previous researches indicated that BRCA1 in module 1 was associated with risk of estrogen-receptor-negative breast cancer ( Milne et al, 2017 ), NFE2L2 in module 3 was related with cell multisystem disorder ( Huppke et al, 2017 ), and TP53 in module 5 was related with human immunodeficiency virus-related head and neck squamous cell carcinoma ( Gleber-Netto et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, isoflavones are a type of naturally occurring isoflavonoids, which act as phytoestrogens in mammals, their targets were mainly distributed in module 1, 2, and 5 ( Supplementary Figure 6 ). Previous researches indicated that BRCA1 in module 1 was associated with risk of estrogen-receptor-negative breast cancer ( Milne et al, 2017 ), NFE2L2 in module 3 was related with cell multisystem disorder ( Huppke et al, 2017 ), and TP53 in module 5 was related with human immunodeficiency virus-related head and neck squamous cell carcinoma ( Gleber-Netto et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, upregulation of NRF2 in aging may improve cell function and stress resistance, which may in turn increase longevity. However, as NRF2 hyperactivity has been associated with cancer susceptibility and poor prognosis [35] , and activating inborn de novo mutations in NRF2 gene cause an early onset multisystem disorder [36] , it is important to understand the natural regulation of NRF2 function in aging for rational design of NRF2 targeted therapies against age-related disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, de novo mutations in human NRF2 gene that induce NRF2 were recently identified (Huppke et al., ), and the cases with the NRF2 induction displayed mild developmental delay, short stature and delayed bone age (Huppke et al., ). The phenotypes observed in the cases are consistent with the phenotype we have observed in the NEKO mice, including the small body length and low bone density.…”
Section: Discussionmentioning
confidence: 99%